“Smenovekhovtsy” Movement and Realities of Soviet Society of 1920-ies - V. N. Azarov (Научный диалог, 2018)
The issues linked with the emergence of “smenovekhovtsy” movement among the Russian emigration in the early 1920-ies are considered. Special attention is paid to the analysis of the key position of “smenovekhovtsy” ideology about the inevitable rebirth of the Bolshevik regime in conditions of implementation of the new economic policy (NEP). The author dwells on the reasons for the formation of “smenovekhovtsy” ideas about the future of the country. It is shown that these views did not correspond to the political and socio-economic realities of Soviet society in the 1920-ies. Attention is paid to the evaluation of “smenovekhovtsy” ideology in the light of political struggle in the administration of the Bolshevik party in the period under review. The question of the moral choice of the Russian intelligentsia is raised in connection with the question of the need for cooperation with the Bolsheviks raised by “smenovekhovtsy”. A review of the correspondence of the most famous ideologist of “smenovekhovtsy” N. V. Ustryalov with his personal friend N. A. Tsurikov is made. The author proceeds from the fact that this correspondence is one of the most striking examples of the depth and dramatic split among Russian immigrants in the 1920-ies. It is concluded that the illusory and erroneous ideas about the prospects of development of Soviet society became the cause of the tragic personal fate for many of “smenovekhovtsy” who returned home from exile and became the victims of Stalinist repression of the 1930-ies.